History of the northwest coast [electronic resource] - Bancroft, Hubert Howe, 1832-1918 (San Francisco : History Co., 1890)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 14095-14097. "In two volumes. Vol. I--1543-1800." Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44